Hubungan Kelainan Letak Janin, Preeklampsia dan Ketuban Pecah Dini dengan Sectio Caesaria di RSUD Dr. H. Mohamad Rabain Muara Enim - Rizka Ameliah; Erma Puspita Sari; Siti Aisyah Hamid (Universitas Batanghari Jambi, 2022)
Caesarean section is a labor process in which the foetus is delivered through a surgical incision in the abdominal wall and uterus with the requirements that the uterus is in the intact condition and the baby’s weight must be more than 500 grams. This study was aimed to find out the correlation between foetus position, preeclampsia and premature rupture of membranes with caesarean section at Dr. H. Mohamad Rabain Regional Public Hospital Muara Enim year 2020. This study applied analytical survey method using cross sectional approach. The population in this study was 555 respondents and the samples who were taken by applying systematic random sampling technique were 84 respondents. The data used in this study were secondary data. These data were then analysed using chi-square statistics. Based on the result of bivariate analysis, it was found out that there was a correlation between foetus position and caesarean section that is 29.8%. Chi-square test result showed ρ value = 0.000. There was also a correlation between preeclampsia and caesarean section that is 14.3%. Chi-square test result showed ρ value = 0.022. There was a correlation between premature rupture of membranes and caesarean section that is 21.4%. Chi-square test result showed ρ value = 0.001. It can be concluded that there was a correlation between foetus position, preeclampsia and premature rupture of membranes with caesarean section at Dr. H. Mohamad Rabain Regional Public Hospital Muara Enim year 2020. It is suggested that the result of this study be able to give general descriptions of factors correlated with caesarean section. In addition, it can also be used as a means to consider so it can decrease the number of caesarean sections.